Sorrow, coping and resiliency: Parents of children with cerebral palsy share their experiences - Whittingham, K.; Wee, D.; Sanders, M.; Boyd, Roslyn (2013)
Purpose: To explore the grieving, coping and resiliency experiences of parents of children with cerebral palsy (CP) and to investigate the suitability of chronic sorrow theory as a framework to understand those experiences. Methods: This study combined focus groups with a web-based cross-sectional survey to explore chronic sorrow in parents of children with CP. Eight parents of children with CP participated in focus groups. The discussion was transcribed verbatim and thematic analysis was performed. A further 94 parents participated in the web-based survey study in which they completed the Adapted Burke Questionnaire on chronic sorrow. A content analysis of responses was used to confirm the primary qualitative analysis. Results: The reports of parents in the focus group were consistent with chronic sorrow theory, as were the responses of parents to the web-based survey. Some parents found the diagnosis itself a distressing time whereas others found it a relief. Parents reported that times of medical and allied health intervention were particularly challenging. Conclusion: Chronic sorry theory is a useful way of understanding the experiences of parents of children with CP. It is recommended that health practitioners are mindful that, even years after diagnosis, parents of children with CP may experience intensified chronic sorrow symptoms following a triggering event and that this is normal. Implications for Rehabilitation This study suggests that chronic sorrow theory is a suitable framework in which to understand the experiences of parents of children with CP. Parents of children with CP may experience intensified grief following a triggering event, even years after diagnosis. This recurring grieving process is healthy and normal with many parents demonstrating resilience by using an array of coping strategies or seeking support from health professionals. © 2013 Informa UK, Ltd.